2022
DOI: 10.1371/journal.pone.0268706
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Yersinia enterocolitica from foods in Apulia and Basilicata regions (Italy) by conventional and modern methods

Abstract: Yersiniosis is the third most reported food-borne zoonosis in Europe. The aim of the present study was to perform the search for Yersinia enterocolitica in food samples collected from Apulia and Basilicata regions (Southern Italy) and to characterize any isolates by classical and modern analytical methods. A total of 130 samples were analyzed between July 2018 and July 2019: most of them were raw milk and dairy products made from it. Furthermore, 8 out of 130 samples were individual milk samples collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…Under these considerations, the relationship between foods and human disease is still strongly debated as the "nonpathogenic" biotype 1A is frequently isolated from foods (Le Guern et al, 2016;Guiller et al, 2021). Even in the present research all the isolated strains were negative for the detection of ail gene as reported by other authors (Mancini et al, 2022). Furthermore, all the Y. enterocolitica strains isolated from diseased people in Umbria region were positive for ail gene detection (Primavilla et al, 2017) even in the same period of observation (data not reported).…”
Section: Articlesupporting
confidence: 58%
See 1 more Smart Citation
“…Under these considerations, the relationship between foods and human disease is still strongly debated as the "nonpathogenic" biotype 1A is frequently isolated from foods (Le Guern et al, 2016;Guiller et al, 2021). Even in the present research all the isolated strains were negative for the detection of ail gene as reported by other authors (Mancini et al, 2022). Furthermore, all the Y. enterocolitica strains isolated from diseased people in Umbria region were positive for ail gene detection (Primavilla et al, 2017) even in the same period of observation (data not reported).…”
Section: Articlesupporting
confidence: 58%
“…2006) but Y. enterocolitica is reported also in other animal species (ZhiChao et al, 2019;Arden et al, 2022). In foods Y. enterocolitica isolation is reported from meat, milk and dairy products and fresh vegetables (Bonardi et al, 2018;Fois et al, 2018;Espenhain et al, 2019;Piras et al, 2021;Mancini et al, 2022). The microorganism can resist in food under different environmental situations, even in not culturable form, and can grow under refrigeration conditions (Fredriksson-Ahomaa, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…All the presumptive Vibrio spp. isolates were identified at species level based on the API ® ID 20E and 20NE systems (BioMérieux, Nürtingen, Germany), the halotolerance test with various concentrations of NaCl (0, 6 and 10%), and the MALDI-TOF MS (Bruker Daltonics, Bremen, Germany) procedure by the direct transfer method, as previously described [ 25 ]. Moreover, the isolates recognised as V. parahaemolyticus , V. cholerae , and V. vulnificus were confirmed by the conventional PCR method described in Annex C to ISO 21872–1:2017, which considers, also, the detection of V. parahaemolyticus virulence genes ( tdh and trh ).…”
Section: Methodsmentioning
confidence: 99%
“…Th e genus Yersinia spp. belongs to the Enterobacteriaceae family and includes 18 species, of which 3 species, i.e., Y. enterocolitica, Y. pseudotuberculosis, and Y. pestis, cause infection in humans and animals [2]. Y. enterocolitica was categorized into two subspecies based on 16s rRNA gene type: Y. enterocolitica subsp.…”
mentioning
confidence: 99%